Information seeking behaviour of SME entrepreneurs in the hospitality industry - Victoria, Jonathan; Salina, Zawawi; Nur Fatihah, Abdullah Bandar (Pustaka Negeri Sarawak, 2024)
In the era of Industry 4.0, the value of information has become even more critical to the success of small hospitality firms. For entrepreneurs in this sector, the ability to seek accurate and timely information is essential. Despite its significance, research on the information-seeking behaviour of entrepreneurs in the hospitality industry remains limited. This paper presents findings from a case study that explores the information-seeking behaviours of hospitality entrepreneurs in Kuching, Malaysia. Data was collected from ten informants through semistructured interviews. The results indicate that entrepreneurs require information related to business operations, advisory and regulatory compliance, marketing, technology, networking, human resources, and financing. While these entrepreneurs utilize both formal and informal sources of information, there is a noticeable preference for informal sources. The study identifies barriers to effective information seeking, including a lack of networking skills, limited time, and insufficient technological proficiency. The findings suggest that hospitality entrepreneurs should enhance their information and social competencies. Additionally, educators, policymakers, information officers, and related government agencies are encouraged to support these small business entrepreneurs in meeting their information needs,particularly in the context of digitalization.